Effect of different constraints on coordination and performance in overarm throwing. - van den Tillaar, R. (2003)
This thesis investigated the effect of the following constraints: body anthropometrics, gender, maximal isometric strength, type of training program, instruction and ball weight. These constraints were investigated in relation to the coordination and performance (i.e. velocity and accuracy) in overarm throwing of experienced handball players. Instruction emphasising accuracy and/or velocity of throwing performance influenced the maximal ball velocity but showed no effect on accuracy. The difference in ball velocity was a result of the difference in maximal linear velocity of the upper body segments together with their timing. The research also showed that body size had a strong positive effect on the throwing performance and isometric strength. Throwing velocity appeared to be affected by gender when size was expressed by mass or height. However, this dependence was completely explained for by size differences when expressed as fat free body mass (FFM). For strength, no gender effect was found at all. This finding strengthens the notion that gender difference is based on difference in muscle bulk and that FFM, as an approximation for skeletal muscle mass, is the best measure to express body size when related to physical performance. Projectile mass affects the release velocity. A linear negative relationship between ball mass and maximal ball velocity, as well as between force and maximal ball velocity was observed. The main contributors to the total ball velocity at release were the internal rotation of the shoulder (63 ) and elbow extension (32 ). Furthermore, it was found that technique was not affected when the ball mass was increased nor when instructions were changed, as was indicated by the invariance of the relative timing of the upper body segments. There are also found indications that the generally accepted proximal-distal sequence did not exist in overarm throwing. No clear answer can be given to the question which type of strength training increases throwing performance (velocity). However, training studies that involved throwing with underweight balls seemed to have a clear positive effect on the throwing velocity. Training with overweight balls, medicine balls or general strength training with load lower than 12 RM gave contradictive results.